2022
DOI: 10.3390/ijerph19169998
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Coupling Coordination between New-Type Urbanization and Water Ecological Environment and Its Driving Factors: Evidence from Jiangxi Province, China

Abstract: With the rapid development of urbanization, problems such as the degradation of water ecological environment have emerged. How to improve the water ecological environment in the process of urbanization has become one of the urgent problems facing policy makers. This paper studies the coupling coordination relationship between new-type urbanization and water ecological environment, with the purpose of using insights gained from the study to help improve the quality of water ecological environment and promote su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…Moreover, the regression results of the impact of technological innovation, import and export trade, and foreign capital on water pollution intensity are similar to those reported Yu and Fang et al on the impact factors of environmental pollution [19,30]. The regression results of the impact of urbanization level on water pollution intensity are similar to those reported by Darko et al, Kan et al and Margaret et al on the relationship between urbanization and ecological environment, who found that the effects of urbanization, such as population upsurge, increased industrialization, urban agriculture, and rural-urban migration of persons, exert pressure on the limited water resources in most cities; the urbanization process not only intensifies the emission of water environmental pollution but also improves the water pollution intensity [60][61][62], although these results are inconsistent with the those reported by Al-Mulali et al, Irfan and Shawon, and Kan et al on the relationship between urbanization and ecological environment, who reported an inverted U curve between urbanization level and the overall quality of the water ecological environment [63][64][65].…”
Section: Estimation Resultssupporting
confidence: 85%
“…Moreover, the regression results of the impact of technological innovation, import and export trade, and foreign capital on water pollution intensity are similar to those reported Yu and Fang et al on the impact factors of environmental pollution [19,30]. The regression results of the impact of urbanization level on water pollution intensity are similar to those reported by Darko et al, Kan et al and Margaret et al on the relationship between urbanization and ecological environment, who found that the effects of urbanization, such as population upsurge, increased industrialization, urban agriculture, and rural-urban migration of persons, exert pressure on the limited water resources in most cities; the urbanization process not only intensifies the emission of water environmental pollution but also improves the water pollution intensity [60][61][62], although these results are inconsistent with the those reported by Al-Mulali et al, Irfan and Shawon, and Kan et al on the relationship between urbanization and ecological environment, who reported an inverted U curve between urbanization level and the overall quality of the water ecological environment [63][64][65].…”
Section: Estimation Resultssupporting
confidence: 85%
“…There are two possible reasons for this: (i) the regional policy has been in place for too short a time, and it takes longer for the policy to respond to ecological status, so the provisional status score is not as good as the pressure and response scores. (ii) China's central government has issued many requirements to cities for environmental protection, which have been fulfilled by various local governments, but superficially and without taking into account the actual situation of each city, resulting in an imbalance between pressure, response and status.In comparison with additional studies with other regions, it was found that many regions within China, such as Jiangxi Province [51] and Shaanxi Province [52], have shown a higher development of urbanisation than ecological environment in recent years, suggesting that there is room for improvement in many regions within China. (1) Accelerating the urbanization process and improve the level of population urbanization and spatial urbanization.…”
Section: Problems Faced By the Huaihe Eco-economic Belt In Terms Of E...mentioning
confidence: 83%
“…There is an inverted U curve between urbanization level and the level of water ecological civilization. Darko et al, Kan et al, and Margaret et al believe that the effects of urbanization, such as population upsurge, increased industrialization, urban agriculture, and rural-urban migration of persons exert pressure on the limited water resources in most cities; the urbanization process has a negative impact on the overall quality of the water ecological environment, which not only intensifies the emission of water environmental pollution, but also inhibits the water environmental absorption capacity [44][45][46]. The regression results are similar to those of Al-Mulali et al and Irfan and Shaw on the relationship between new-type urbanization and ecological environment in 93 countries and South Asian countries, respectively [47,48], but they are inconsistent with the results of Li on the relationship between new-type urbanization and ecological environment; he found an anti-N-shaped relationship between urbanization and ecological environment in China [49].…”
Section: Discussionmentioning
confidence: 99%